More Than Just Surviving: Rebellion Against Patriarchy in the English Translation of Han Kang’s The Vegetarian - Tabor, Dominika (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2024)
The article analyzes the English translation of the Korean novel The Vegetarian (2015) by Han Kang in light of the impact of a patriarchal society on a woman's life. In the article, I analyze the English version as a standalone novel rather than a translation from Korean due to various instances of mistranslations and omissions. The narrative tells the story of Yeong-hye, a Korean woman who one day becomes an eponymous vegetarian and stops eating meat. The more committed Yeong-hye is to her dietary choice, the more aggressive her family becomes, perceiving her decision as absurd and foolish. The novel's central theme, unlike the novel's title may suggest, is not vegetarianism but rebellion and the silent suffering of a woman trapped in a patriarchal world that does not understand her. The study incorporates Gilbert and Gubar's concept of the “angel in the house” and Timothy Morton's distinction between Life and